Mantua, City of Water between History and the Present - Pierfranco Galliani; Cassandra Cozza (Agathón)
Ever since the Middle Ages, the relation between nature and architecture has characterised Mantua’s environmental situation and urban form. The artificial formation of the lakes transformed the city into a peninsula and placed it in the state of a comprehensive artefact whose complexity had to be considered in the case of every new intervention. Water is the limen of the city’s essence: the boundary separating it from the countryside and a defensive barrier; a threshold between nature and artifice by means of embankment-bridges; and a medium of the fluvial interchange. Some design experimentations delineate the principles of a critical continuity in which renewal means belonging to the stratification of the history of the places.